Light‐Activated Gas Sensors: Optically Activated 3D Thin‐Shell TiO2 for Super‐Sensitive Chemoresistive Responses: Toward Visible Light Activation (Adv. Sci. 3/2021). Issue 3 (3rd February 2021) - Cho, Donghwi; Suh, Jun Min; Nam, Sang‐Hyeon; Park, Seo Yun; Park, Minsu; Lee, Tae Hyung; Choi, Kyoung Soon; Lee, Jinho; Ahn, Changui; Jang, Ho Won; Shim, Young‐Seok; Jeon, Seokwoo
Abstract : To take advantage of nanostructures beyond their large surface area for light‐activated gas sensing, in article number 2001883, Seokwoo Jeon, Young‐Seok Shim, Ho Won Jang, and co‐workers introduce a new class of UV‐activated sensing of rationally designed highly periodic 3D TiO2 . The 3D TiO2 facilitates 55 times enhanced light absorption and ultra‐sensitive NO2 sensing properties with a detection limit of ∼200 ppt at room temperature.